‘DAMNATIO MEMORIAE’ JAKO ŚRODEK WALKI Z OPOZYCJĄ POLITYCZNĄ - Dyjakowska, Marzena (Zeszyty Prawnicze, 2016)
‘DAMNATIO MEMORIAE’ AS A KIND OF PENALTY FOR REPRESSING THE MEMORY OF THE PUBLIC ENEMY Summary The paper presents damnatio memoriae – a kind of penalty for repressing the memory of the public enemy in ancient Rome. This penalty might be imposed by decree of the senat (or of the emperor) in case of the posthumous prosecution or conviction of a person on charges of treason (crimen maiestatis). Damnatio memoriae (or – in a technical, juridical expression – memoria damnata) was not intended to destroy recollection of a person who was condemned, but rather to dishonor the record of such a person. Penalties for repressing the memory, enacted separately or together, included for instance the eradication of visual representations of the person, in particular of statues, busts, coins and medallions, or the erasure of his name. The representations of the condemned, which already existed, were to be altered or destroyed, and there were to be no representations in the future. Some statues have meen modified – removed, replaced or reworked to represent someone new. The name of the enemy might be erased from some public documents (especially from the state lists of officials – the fasti) and inscriptions. Historians were sometimes not allowed to use names of those, who have suffered the penalty in question. There were also some decrees of the senat requiring the family to discontinue the use of a particular element of the name of public enemy (praenomen or cognomen). The penalties included a ban of the observance of the funeral and mourning. The family of convicted was forbidden to keep his portraits within the home or to mour for him. The body of the public enemy could be denied to his relatives and not buried. His bust could not be paraded at the funeral ceremonies of members of his family. According to Tacitus, who used to criticize the political repressions of the early emperors, damnatio memoriae is a vain penalty – memory will survive.